2019
DOI: 10.1186/s13024-019-0334-4
|View full text |Cite
|
Sign up to set email alerts
|

A circuit view of deep brain stimulation in Alzheimer’s disease and the possible mechanisms

Abstract: Alzheimer’s disease (AD) is characterized by chronic progressive cognitive deterioration frequently accompanied by psychopathological symptoms, including changes in personality and social isolation, which severely reduce quality of life. Currently, no viable therapies or present-day drugs developed for the treatment of AD symptoms are able to slow or reverse AD progression or prevent the advance of neurodegeneration. As such, non-drug alternatives are currently being tested, including deep brain stimulation (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 117 publications
0
28
0
1
Order By: Relevance
“…The ENT is divided into the ENTm and ENTl based on their distinctive cytoarchitecture and connectivity patterns. The ENTm contains strongly position-related (spatial) neurons, whereas the ENTl contains neurons encoding object information, attention, and motivation (Yu et al, 2019). In this study, we found that the ENTl and ENTm demonstrated the opposite projecting patterns to the NAcLS, NAcMS, and NAcC.…”
Section: Discussionmentioning
confidence: 50%
“…The ENT is divided into the ENTm and ENTl based on their distinctive cytoarchitecture and connectivity patterns. The ENTm contains strongly position-related (spatial) neurons, whereas the ENTl contains neurons encoding object information, attention, and motivation (Yu et al, 2019). In this study, we found that the ENTl and ENTm demonstrated the opposite projecting patterns to the NAcLS, NAcMS, and NAcC.…”
Section: Discussionmentioning
confidence: 50%
“…Alzheimer's disease (AD) is the most common age-related neurodegenerative disorder characterized by abnormal accumulation and deposition of various amyloid-β (Aβ) peptides derived from amyloid-β precursor protein (APP), formation of neurofibrillary tangles containing hyperphosphorylated tau, synaptic dysfunction, neuroinflammation, neuronal death, and cognitive decline (Crews and Masliah, 2010;Huang and Mucke, 2012;Guerreiro and Bras, 2015;Kocahan and Dogan, 2017;DeTure and Dickson, 2019). So far no effective therapies are available to cure this devastating disease (Yu et al, 2019). Since social and financial burdens for AD have become enormous as our population ages, there is an urgent need to elucidate the detailed molecular mechanisms underlying AD pathogenesis, so that new targets may be identified for therapeutic development.…”
Section: Introductionmentioning
confidence: 99%
“…Seven patients had syncope and/or falls; two patients had altered mental status; two patients were involved in seizures or possible seizure; one patient was involved in agitation in a delayed; three patients were involved in a skin infection, suspected aortic valve endocarditis, and rigidity. and Drevets, 2010); ILN and MTN are important components forming cortico-thalamo-cortical pathways (Saalmann, 2014); NBM participates in the base forebrain cholinergic circuit; and the fornix, MT, ANT, EC, and CA1 (hippocampus) are nodes in the Papez circuit (Yu et al, 2019). Figure 2 shows a schematic representation of these targets in the brain.…”
Section: Scharre Et Al (2018)mentioning
confidence: 99%
“…At present, there is little direct research on the mechanism of action of DBS in AD, and various hypotheses (changing the electrical activity of neurons, promoting neurogenesis and neurotransmitter release, etc.) have been proposed to explain its potential mechanism of action (Hescham et al, 2013a ; Laxton and Lozano, 2013 ; Kuhn et al, 2015a ; Aldehri et al, 2018 ; Jakobs et al, 2019 ; Yu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%